Brown adipose tissue volume and 18F-fluorodeoxyglucose uptake are not associated with energy intake in young human adults. Issue 2 (11th December 2019) - Sanchez-Delgado, Guillermo; Acosta, Francisco M; Martinez-Tellez, Borja; Finlayson, Graham; Gibbons, Catherine; Labayen, Idoia; Llamas-Elvira, Jose M; Gil, Angel; Blundell, John E; Ruiz, Jonatan R
ABSTRACT: Background: Several studies have explored the role of human brown adipose tissue (BAT) in energy expenditure. However, the link between BAT and appetite regulation needs to be more rigorously examined. Objectives: We aimed to investigate the associations of BAT volume and 18 F-fluordeoxyglucose ( 18 F-FDG) uptake after a personalized cold exposure with energy intake and appetite-related sensations in young healthy humans. Methods: A total of 102 young adults (65 women; age: 22.08 ± 2.17 y; BMI: 25.05 ± 4.93 kg/m 2 ) took part in this cross-sectional study. BAT volume, BAT 18 F-FDG uptake, and skeletal muscle 18 F-FDG uptake were assessed by means of static 18 F-FDG positron-emission tomography and computed tomography scans after a 2-h personalized exposure to cold. Energy intake was estimated via an objectively measured ad libitum meal and three nonconsecutive 24-h dietary recalls. Appetite-related sensations (i.e., hunger and fullness) were recorded by visual analog scales before and after a standardized breakfast (energy content = 50% of basal metabolic rate) and the ad libitum meal. Body composition was assessed by a whole-body DXA scan. Results: BAT volume and 18 F-FDG uptake were not associated with quantified ad libitum energy intake (all P > 0.088), nor with habitual energy intake estimated from the 24-h dietary recalls (all P > 0.683). Lean mass was positively associated with both the energy intake from the ad libitum meal (β: 17.612, R 2 = 0.213; P < 0.001) and the habitual energy intake (β: 16.052, R 2 = 0.123; P = 0.001). Neither the interaction BAT volume × time elapsed after meal consumption nor that of BAT 18 F-FDG uptake × time elapsed after meal consumption had any significant influence on appetite-related sensations after breakfast or after meal consumption (all P > 0.3). Conclusions: Neither BAT volume, nor BAT 18 F-FDG uptake after cold stimulation, are related to appetite regulation in young adults. These results suggest BAT plays no important role in the regulation of energy intake in humans. This trial was registered at clinicaltrials.gov as NCT02365129.